Survivors of the Shoah: Interviewee: Ida Banda, Part I (Survivors of the Shoah Visual History Foundation, 1999)
Shoah Foundation interview code: 49587 Duration: 01:55:00 Interview with Holocaust survivor Ida Banda. The tape is part of a collection of 10 interviews provided to OSA by the Survivors of the Shoah Visual History Foundation. Interviewer: Anna Mérei.